A solar assisted desalination system using heat pump - Hawlader, Mohammad Nurul Alam; Leong , Chiing Yang (IIUM Press, 2011)
This paper includes results of an investigation carried out on a desalination plant which consists of a direct expansion solar assisted heat pump (DXSAHP) coupled to a single-effect evaporator unit. The working fluid used in the heat pump is R134a. The distillate is obtained via falling film evaporation and flashing in the evaporator. Experiments have been conducted under both day and night meteorological conditions in Singapore and the effects of solar irradiation and compressor speed on the performance of the system have been investigated. From the experiments. the performance ratio was found to vary between 0.43 and O.RR, the average coefficient of performance was 8 and the highest distillate production recorded was 1.38kg/hr.